Vulnerabilidade político-institucional: a complexa dimensão do risco de desastre - Silveira, Tânia Maria (2024)
Disasters are increasingly recurring at national and global levels. Vulnerability is a polysemic concept used in different fields of knowledge to understand specific problems. However, within the field of disaster studies, vulnerability is a specific problem whose study has been driven by the escalation of this phenomenon and its damaging effects on people, communities, systems and assets susceptible to hazards. This thesis investigates the causes of the failure of the Fundão dam in Mariana (MG) in 2015. It aims to identify the political-institutional factors and processes that exacerbated the conditions of vulnerability in the Samarco case. As a case study, it uses Robert Yin's (2005) concept as a methodological reference, as well as qualitative methods and techniques used in the social sciences. The theoretical proposition that reflected the set of research questions was based on the concept of politicalinstitutional vulnerability as a dimension of disaster risk. The institutional dimension of vulnerability encompasses both the context and the process by which institutions are weak in ensuring compliance with safety standards, or how they ignore their duty to ensure compliance with regulations to prevent, mitigate, and recover from the effects of a hazardous event. The findings of this thesis show that the Fundão dam collapse had devastating consequences. Political and institutional vulnerability exacerbated risk conditions, resulting in multiple impacts that persist over time. Samarco Mineração S.A. and its parent companies, Vale S.A. and BHP Billiton Brasil Ltda., expanded production beyond what was sustainable, disregarding laws and safety standards. At the institutional level, the research revealed omissions and shortcomings in regulations, as well as non-compliance with the rules established by public licensing and inspection bodies, which allowed the dam to operate without guaranteeing compliance with safety standards. The analysis of the context revealed challenges in the public governance of disaster risk and in the regulation of the negative externalities of iron ore mining. In summary, the thesis confirms the theoretical contributions in the disaster literature that vulnerability to disaster hazards is a complex and dynamic relational expression because it involves multiple interrelated factors. In other words, vulnerability is not an isolated concept. intrinsically connected to other elements such as the environment, infrastructure, communities, and social and political systems. It is complex because it cannot be reduced to a single cause or variable, and it is dynamic because it evolves over time. This means that disaster vulnerability is a multifaceted concept that requires a holistic and adaptive approach to minimize risks and adverse impacts.